Komunikasi Interpersonal Dan Budaya Kerja Dalam Meningkatkan Hubungan Dengan Pegawai Di Klinik Pelangi Bunda Medika - Ramdhan, Arfian Surya Suci; Zulfikar, Meiby; Hasanah, Uswatun; Agustin, Dewi Ilma; Pramudita, Sindy (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Internal communication can be understood as the foundation and building blocks of an organizational culture. The existence of an organizational culture that is firmly adhered to by employees will greatly support the process of achieving the company's main goals (Agustini & Purnaningsih, 2018). This research was conducted using a qualitative approach, which is descriptive in nature and Human Relations Theory. The data collection method was carried out using in-depth interviews and observation methods. (Isniyunisyafna, & Isfiantie S, 2020). For employees, the role of effective internal communication in improving good and sustainable relationships is very important. Because good internal communication can strengthen social relationships, increase collaboration, solve problems, develop leadership skills.This research explores the urgency of internal communication in building a strong organizational culture, strengthening social relationships, and improving company performance. Carried out using a qualitative approach and Human Relations Theory, with in-depth interview and observation methods.The importance of internal communication in building a strong organizational culture and supporting the achievement of company goals. The role of internal communications in improving social relationships, collaboration, and leadership skills. A qualitative approach and Human Relations Theory are used to understand the role of internal communication in organizational culture. Data collection methods through in-depth interviews and observation.Analyze the urgency and role of internal communication in building a strong organizational culture. Investigate the impact of internal communications on social relationships, collaboration, and leadership skills. Enrich understanding of the importance of internal communication in the context of organizational culture. Provides insight into effective internal communication practices in improving company performance. Provides a framework for the development of more effective internal communications strategies.